One-trocar-assisted pyeloplasty: An attractive alternative to open pyeloplasty - Antonio Marte; Alfonso Papparella (Wolters Kluwer Medknow Publications, 2015)
Background: To survey the effects of one-trocar-assisted pyeloplasty (OTAP) in the treatment of ureteropelvic junction obstruction (UPJO) in kids. Materials and Methods: Forty-four children (±3.5 years) were submitted to OTAP procedure. A flank incision under the XII rib was made, the Gerota's fascia was achieved and a balloon Hasson trocar with an operative telescope inserted for retroperitoneal access. The renal pelvis and ureter were isolated and exteriorised. Forty-two patients underwent Anderson-Hynes dismembered and one Fenger pyeloplasty . One patient was converted to an open procedure. Two patients presented an aberrant crossing vessel. In all patients, a double J stent was positioned. The operative time and length of stay (LOS) were evaluated. Renal scan and ultrasound (US) were utilised to evaluate the results from 6 to 12 months. Results: OTAP was successful in all but 1 patient. Mean operative time and LOS were 128 min and 3,5 days. We had four operative complications (9.09%). The US and a nuclear scan confirmed the resolution of the UPJO in all patients except one with the Fenger pyeloplasty who had an open Anderson-Hynes. Conclusions: The combination of retroperitoneoscopic and open procedures for dismembered pyeloplasty offers a simple, time-saving method in a minimally invasive fashion with low morbidity for patients with UPJO.